Linguagens e diversidades : uma leitura de Jorge Amado e Boaventura Cardoso - Ribeiro, Gilvan Procópio (2008)
This work intends to develop a comparative reading between the Brazilian writer Jorge Amado and the Angolan writer Boaventura Cardoso, by considering the colonial legacy and its apropriation. For that its departing point is an anlysis of language variations that appears in two remarkable aspects in the novels of both writers: ideology and religiosity, and in what ways yhese variations are able to establish identity patterns in as attempt to criate a foundational discourse. .